2007
DOI: 10.1007/s00502-007-0497-5
|View full text |Cite
|
Sign up to set email alerts
|

CIRED 2007: Berichte aus den Sessionen

Abstract: 1.1 Einleitung 102 Beiträ ge wurden ausgewä hlt und auf die vier Bereiche Hauptsession, Round Table-Diskussion, Forschungs-und Entwicklungsforum und Poster-Session aufgeteilt. Kriterien waren die Qualitä t der Arbeit, geringe Redundanz bei Themen und Autoren, die zur Verfü gung stehende Zeit in der Hauptsession und die Aktualitä t des Themas. Etwa die Hä lfte behandelte Netzkomponenten, die in Betrieb sind, und die andere betraf Innovationen. Die Beiträ ge wurden in folgende vier Blö cke eingeteilt " Block 1: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It can be caused by a variety of etiologic factors, including myocardial infarction, hypertension, amyloidosis, and so on (John and Piotr, 2011). The exact evidence has indicated that concentrations of catecholamines are elevated in the development of heart failure, resulting in morphological alterations of the heart or left ventricular hypertrophy (Bristow et al, 1985; Lefkowitz et al, 2000). Isoproterenol (ISO), one of the catecholamine adrenergic receptor agonists, has been proved to cause myocardial necrosis, cardiac hypertrophy, fibroblast proliferation, and abnormality of diastolic and systolic functions by subcutaneous injection, and these changes of heart induced by ISO can mimic the pathological changes of cardiac tissue in the process of human heart failure (Benjamin et al, 1989; Oudit et al, 2003; Christian et al, 2005; Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can be caused by a variety of etiologic factors, including myocardial infarction, hypertension, amyloidosis, and so on (John and Piotr, 2011). The exact evidence has indicated that concentrations of catecholamines are elevated in the development of heart failure, resulting in morphological alterations of the heart or left ventricular hypertrophy (Bristow et al, 1985; Lefkowitz et al, 2000). Isoproterenol (ISO), one of the catecholamine adrenergic receptor agonists, has been proved to cause myocardial necrosis, cardiac hypertrophy, fibroblast proliferation, and abnormality of diastolic and systolic functions by subcutaneous injection, and these changes of heart induced by ISO can mimic the pathological changes of cardiac tissue in the process of human heart failure (Benjamin et al, 1989; Oudit et al, 2003; Christian et al, 2005; Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%